The experiential world of the Oncology nurse - Dalena van Rooyen; Laetitia le Roux; W J Kotzé (AOSIS, 2008)
In her experiential world, the oncology nurse experiences unique, challenging and rewarding relationships in a multidimensional, dynamic way. The aim of this study was to describe, from her viewpoint and perspective, how she experiences and reacts to this world. Through this study the researcher wants the oncology nurse's voice to be heard, the richness of her story acknowledged and the derived data to be applied to the benefit of the field of oncology. In-depth, unstructured phenomenological interviews provided the saturated data from which the uniqueness of the world of the oncology nurse unfolded as the uniqueness of the oncology patients and their world emerged clearly. Findings show that the oncology nurse, attending to the cancer patients and their family, experiences many different relationships. The uniqueness of the oncology nurse-patient relationship is described as unlike any other nurse-patient relationship. The challenging interpersonal relationships with management and other members of the multiprofessional team, as experienced from the perspective of the oncology nurse, are also highlighted. Furthermore, a unifying intrapersonal relationship with the self was identified. This enables the oncology nurse to be both on the giving and receiving end of the intensely emotional environment she works in, explaining, at least partly, the high job satisfaction that permeated the interviews in this study. Recommendations for nursing practice, education and research were formulated. Opsomming In haar leefwêreld ondervind onkologieverpleegkundige unieke, uitdagende en belonende verhoudinge op 'n multidimensionele en dinamiese wyse. Die doel van hierdie studie was om 'n beskrywing van die onkologieverpleegkundige se ervarings van en reaksie op haar leefwêreld vanuit haar oogpunt en perspektief. Deur middel van hierdie studie wil die navorser die stem van die onkologieverpleegkundige gehoor laat word, die rykdom van haar verhaal erken en die verkrëe data toepas tot voordeel van die onkologieveld. In-diepte, ongestruktureerde fenomenologiese onderhoude het die versadigde data verskaf waaruit die unieke eienskappe van die onkologieverpleegkundige se wêreld ontvou het soos wat die uniekheid van onkologiepasiënte en hulle wêreld duidelik na vore getree het. Die resultate toon dat die onkologieverpleegkundige wat na die kankerpasiënte en hulle familie omsien, 'n verskeidenheid verhoudinge ervaar. Die unieke aard van die verhouding tussen die onkologiepasiënt en die verpleegkundige word beskryf as anders as enige ander pasiënt-verpleegkundigeverhouding. Die uitdagende interpersoonlike verhoudinge met bestuur en ander lede van die multiprofessionele span, soos ervaar deur die onkologie-verpleegkundige, word ook uitgelig. Voorts is 'n unieke, saambindende intrapersoonlike verhouding met die self ook geïdentifiseer. Hierdie verhoudinge stel onkologie-verpleegkundiges daartoe in staat om beide te gee én te ontvang in hierdie intens emosionele wêreld waarin hul werk. Die hoë werksbevrediging wat uit die onderhoude na vore gekom het, word ten minste gedeeltelik deur hierdie verhoudinge verklaar. Aanbevelings ten opsigte van verpleegpraktyk, onderrig en navorsing is geformuleer. The feminine gender is used at times in this article to refer to the oncology nurse. It is acknowledged, however, that there are both male and female oncology nurses.